KEMAMPUAN RASIO KEUANGAN SEBAGAI ALAT UNTUK MEMPREDIKSI PERINGKAT OBLIGASI (PT PEFINDO) - Maylia Pramono Sari (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
Bond rating is a guide to investor who intends to buy bond because that rating gives informative statement and giving signal about company’s debt failure possibility. The purposes of this research are getting more empirical evidendence about the ability of financial ratios in forming model that used to predict bond rating. The results show that discriminant analysis results are significant ratios. It used 38 manufactures companies with 160 bond issuances from 1999 to 2004. The bond predicting models have accuracy 96,9 % for descriminant analisis. It means the model can be used as tool in predicting bond rating for Indonesian manufacturer company in Indonesia. Key Words : bond rating, financial ratios (leverage, likuidity, solvability, profitability and producttivity), descriminant analysis (MDA) and logistic regression.